Navigating dictionary space: the findability of English collocations in a general learner’s dictionary (LDOCE4) and special-purpose dictionary of collocations (OCD) - Lew, Robert; Radłowska, Magdalena (Cambridge Scholars Publishing, 2010)
The present study undertakes to assess the success with which intermediate pre-university Polish learners of English are able to locate English collocations in two learners’ dictionaries, representing two different dictionary types. The first of these is a general dictionary for learners, Longman Dictionary of Contemporary English, fourth edition (LDOCE). The second dictionary is a special-purpose dictionary dealing specifically with collocations, the Oxford Collocations Dictionary (OCD). The collocations are classified into several types for the findability test.
Keywords: Dictionaries; Collocation; Entry navigation